Spectroscopic signatures of an ordered array of independent Ag heptamers. (15th July 2015) - Moras, P; Sheverdyaeva, P M; Pacilé, D; Carbone, C
Abstract: A periodic network of Ag heptamers forms on the carburized W(1 1 0)- R (15 × 12) surface, upon deposition of sub-monolayer amounts of Ag. We investigate the electronic structure and dimensionality of this system by angle-resolved photoemission spectroscopy. The observation of very well-defined Ag 4d-levels confirms the highly ordered growth of size-selected Ag nano-particles on the W(1 1 0)- R (15 × 12) template. The absence of energy dispersion of these states indicates negligible coupling among the Ag heptamers, and points out the local character of the heptamer–substrate interaction. The system can be described as an array of Ag heptamers with fully confined Ag 4d-levels.